1H NMR-based metabolomics of antimalarial plant species traditionally used by Vha-Venda people in Limpopo Province, South Africa and isolation of antiplasmodial compounds. (10th January 2019) - Bapela, M. Johanna; Heyman, Heino; Senejoux, Francois; Meyer, J.J. Marion
Abstract: Ethnopharmacological relevance: The Vha-Venda people living in rural areas of Limpopo Province of South Africa regularly use traditional plant-based medicines to treat malaria. In our earlier publication, twenty indigenous plant species used to treat malaria or its symptoms by Vha-Venda people were evaluated for antiplasmodial activity. The main objective of the current study was to assess the robustness of NMR-based metabolomics in discriminating classes of secondary compounds that are responsible for the observed antimalarial activity and the isolation of antiplasmodial compounds. Materials and methods: Twenty dichloromethane extracts were reconstituted in CDCl3, subjected to 1 H NMR-based metabolomic analysis on a Varian 600 MHz spectrometer and the acquired 1 H NMR spectra were then evaluated collectively using multivariate data analysis (MDA). Principal Component Analysis (PCA) and Orthogonal Projections to Latent Structures–Discriminant Analysis (OPLS-DA) were used to 'globally' discern antiplasmodial profiles. A contribution plot was then generated from the OPLS-DA scoring plot in an attempt to determine the classes of compounds that are responsible for the observed grouping. Further phytochemical analyses were conducted on the lipophilic extracts of Tabernaemontana elegans and Vangueria infausta subsp. infausta . These best candidates were fractionated, purified and their isolated compounds identified based on conventional chromatographic and spectroscopic techniques. Results: The PCA did not separate the acquired profiles according to the detected antiplasmodial bioactivity. Application of a supervised OPLS-DA on the 1 H NMR profiles resulted in a discrimination pattern that could be correlated to the observed antimalarial bioactivity. A contribution plot generated from the OPLS-DA scoring plot illustrated the classes of compounds responsible for the observed grouping. Prominent peaks were observed in the aromatic, sugar-based/N-containing and aliphatic spectral regions of the contribution plot. Two known indole alkaloids were isolated from T. elegans, and identified as tabernaemontanine (IC50 = 12.0 ± 0.8 µM) and dregamine (IC50 = 62.0 ± 2.4 µM). Friedelin (IC50 = 7.20 ± 0.5 µM) and morindolide (IC50 = 107.1 ± 0.6 µM) were isolated from V. infausta subsp. infausta . This is the first report of the rare iridoid lactone, morindolide's antimalarial activity. While these two compounds have been previously identified, this is the first account of their occurrence in the genus Vangueria . Conclusion: The study illustrated the potential of NMR-based metabolomics in discriminating classes of compounds that may be attributed to antiplasmodial activity. Additionally, the study demonstrated the potential of discovering novel antiplasmodial scaffolds from medicinal plants and the rationale for the bioprospecting antimalarial plant species used by Vha-Venda people. Graphical abstract: